Bilateral fusion of mandibular primary teeth - Chalakkal P; Thomas A (Wolters Kluwer Medknow Publications, 2009)
The aim of the report was to highlight the rarity of occurrence of bilaterally fused mandibular primary lateral incisors and canines by virtue of the number of such cases reported in literature; to identify congenital absence of successor teeth;and to evaluate their pulpal morphologies to understand the type of fusion. Clinical observation along with an orthopantomograph and periapical radiographs were used to arrive at a diagnosis. The pulpal morphologies varied in each of the fused teeth although both were fusions of the Complete type. There was congenital absence of the permanent mandibular lateral incisors, bilaterally. It was a case of bilateral fusion of mandibular primary lateral incisors and canines of the Complete type with congenitally absent mandibular permanent lateral incisors. Only 13 such cases have been previously reported in literature.